Sexual problems of urban women in Croatia: Prevalence and correlates in a community sample - Štulhofer, Aleksandar; Gregurović, Margareta; Pikić, Aleksandra; Galić, Ivana (2005)
To asses the prevalence and correlates of female sexual problems in a community sample in the Croatian capital of Zagreb. Method: The study was based on a self-administered postal survey of 1, 170 women 20-60 years old, living in Zagreb. The return rate was 48% (n = 547). Participants not sexually active in the last month (n = 119), and those who self-identified as homosexual or bisexual (n = 31), were excluded from the analyses. The final sample consisted of 384 women. The average age of participants was 38.2 years. Four categories of sexual problems were addressed: inhibited sexual desire, inhibited sexual arousal, inhibited orgasm, and sexual pain disorders. Results: Of the heterosexual women sexually active in the last month, 33.8% experienced sexual problems, with inhibited orgasm being the most frequent problem. Comorbidity was recorded among 10.7% of the participants. Older age was positively related to inhibited desire (β = 0.11, P = 0.05) and inhibited arousal (β = 0.25, P = 0.002), whereas it was negatively related to inhibited orgasm and sexual pain disorders (β = -3.73, P = 0.001 and β = -6.98, P = 0.01, respectively). Length of relationship was positively related to inhibited desire (β = 1.17, P = 0.016). Religious morality was positively related to inhibited desire, inhibited arousal, and sexual pain disorders (β = 0.43, P < 0.001, β = 0.52, P = 0.001, and β = 0.11, P = 0.044, respectively). Intimate communication was negatively related to inhibited desire, inhibited arousal, and inhibited orgasm (β = -2.18, P < 0.001, β = -2.67, P < 0.001, and β = -0.21, P = 0.003, respectively) ; and body image was negatively related to inhibited arousal and sexual pain disorders (β = -1.17, P = 0.026 and β = -0.38, P = 0.042, respectively). Conclusion: Sexual health disturbances among urban Croatian women are frequent. Their prevalence calls for incorporating sexual health issues in the national public health agenda. Multifaceted character of sexual problems is important for adult sexuality education and counseling.
ENG